Extraction, Purification, and Bioactivity of Fucoxanthin from Brown Seaweed Sargassum hystrix - Nungky Mufarocha; Amir Husni; Masagus Muhammad Prima Putra (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. UAE at 45°C for 30 min produced the highest crude extract yield (19.90%). 2. Ethyl acetate:n-butanol (8:2) yielded the highest fucoxanthin fraction (1.31 mg/g). 3. Fucoxanthin fractions showed strong antioxidant activity (DPPH IC₅₀ 86.18±5.06 µg/mL). 4. Purified fractions exhibited strong tyrosinase inhibition (IC₅₀ 76.04±3.24 µg/mL).   Abstract Fucoxanthin is the major carotenoid present in brown seaweeds and exhibits strong biological activities, particularly as an antioxidant and anti-aging agent. However, efficient extraction and purification conditions for fucoxanthin from Sargassum hystrix, along with its functional evaluation, remain limited. This research aimed to establish the most effective extraction conditions for obtaining fucoxanthin from S. hystrix using Ultrasound‑Assisted Extraction (UAE), determine the optimal solvent system for purification, and evaluate the antioxidant and anti-aging activities of both the extracted and purified fucoxanthin. Extraction was carried out using UAE with 96% ethanol at temperatures of 35–45°C and durations of 20–30 min. Purification was conducted through column chromatography using three solvent systems: n‑hexane:acetone (6:4 v/v), methanol:chloroform (7:3 v/v), and ethyl acetate:n‑butanol (8:2 v/v). Fucoxanthin was identified by thin-layer chromatography and fucoxanthin was quantified using reversed-phase high-performance liquid chromatography (HPLC) equipped with a C18 column, while antioxidant activity was measured using the DPPH method and anti-aging activity was assessed via tyrosinase inhibition. The results showed that optimal extraction occurred at 40–45°C for 25–30 min, yielding 18.33–19.9% crude extract, and the ethyl acetate:n‑butanol (8:2 v/v) system produced the highest fucoxanthin fraction yield (8.26–9.54%), with fraction F22 containing the highest fucoxanthin level at 1.31 mg/g. The fucoxanthin fraction displayed markedly enhanced activity, with strong antioxidant capacity (IC₅₀ = 86.18±5.06 μg/mL, an 83.8% improvement over the crude extract) and strong tyrosinase inhibition (IC₅₀ = 76.04±3.24 μg/mL). Overall, fucoxanthin derived from S. hystrix demonstrates substantial promise as an active antioxidant and anti-aging compound for nutraceutical and cosmetic applications, suggesting that future studies should focus on scaling up the extraction and purification process and further elucidating its mechanisms of action and stability in formulated products.